2021
DOI: 10.1186/s13063-020-04993-w
|View full text |Cite
|
Sign up to set email alerts
|

Maximising recruitment to a randomised controlled trial for chronic rhinosinusitis using qualitative research methods: the MACRO conversation study

Abstract: Background Randomised controlled trials (RCTs) are considered the ‘gold standard’ of medical evidence; however, recruitment can be challenging. The MACRO trial is a NIHR-funded RCT for chronic rhinosinusitis (CRS) addressing the challenge of comparing surgery, antibiotics and placebo. The embedded MACRO conversation study (MCS) used qualitative research techniques pioneered by the University of Bristol QuinteT team to explore recruitment issues during the pilot phase, to maximise recruitment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
(53 reference statements)
1
4
0
Order By: Relevance
“…Patient‐related barriers primarily surrounded the acceptability of the treatment arms, which was further complicated by aspects of ED symptomatology, such as high ambivalence. This is consistent with previous literature suggesting patient treatment preference as a key recruitment barrier in randomised controlled trials (RCT; Donovan et al., 2014 ; Elliott et al., 2017 ; McDermott et al., 2021 ). Additionally, AN populations are noted to be challenging to recruit and retain in RCTs due in part to high ambivalence and low treatment acceptability (Halmi, 2008 ; Halmi et al., 2005 ; Vinchenzo et al., 2022 ; Watson & Bulik, 2013 ).…”
Section: Discussionsupporting
confidence: 92%
“…Patient‐related barriers primarily surrounded the acceptability of the treatment arms, which was further complicated by aspects of ED symptomatology, such as high ambivalence. This is consistent with previous literature suggesting patient treatment preference as a key recruitment barrier in randomised controlled trials (RCT; Donovan et al., 2014 ; Elliott et al., 2017 ; McDermott et al., 2021 ). Additionally, AN populations are noted to be challenging to recruit and retain in RCTs due in part to high ambivalence and low treatment acceptability (Halmi, 2008 ; Halmi et al., 2005 ; Vinchenzo et al., 2022 ; Watson & Bulik, 2013 ).…”
Section: Discussionsupporting
confidence: 92%
“…The involvement of the QRI in the NAIROS was also cited by staff as having a positive influence on recruitment rates. As in previous studies, 148,149 research nurses in particular were highlighted by surgeons as being essential to the implementation of the trial at their sites. However, participants also described several challenges in relation to implementation.…”
Section: Collective Action: People's Ability To Take On the Work Need...mentioning
confidence: 60%
“…It has been widely shown that a pre-existing patient treatment preference is a common reason for not taking part in a clinical trial, while the perception of not getting treatment in a placebo arm is something that has been shown to harm recruitment. 31 The presence of a placebo or no-treatment control has been shown to be a frequent barrier to recruitment in cancer trials. 32 Work using the QuinteT recruitment intervention has demonstrated that failing to explore patient preference and difficulties explaining the trial intervention arms were frequent problems in surgical clinical trials.…”
Section: Discussionmentioning
confidence: 99%